Operasi Morfologi Dan Kode Rantai Untuk Menghitung Luas Area Basah Kertas Saring - Nafiatun Sholihah; Agus Harjoko (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
Calculation of wet areas carried out with the help of millimeter block paper has the disadvantage of copying the edges that are less precise and the calculation time is quite long. Another problem is the consistency and accuracy that is generated depends on the subjective factors of the person and one's fatigue. In order for the process to be faster and more consistent, the calculation process using image processing is very necessary. Image preprocessing includes cropping, grayscalling, lowpass filter averaging, convertion to binary image based on otsu thresholding, and complementing images to pixel objects of value 1. Segmentation with morphological operations, including opening operations to remove small objects around objects, Holes Filling operations to fill holes in objects, opening operations again to remove objects other than wet areas. The process of calculating wet areas uses chain code. Based on the results of testing of 81 images, the use of morphological operations is able to produce segmentation of wet areas that approach the original wet area. The scale value affects the accuracy and the best scale is obtained from the use of the ruler. The use of chain code is able to calculate the wet area on filter paper with an average accuracy of 95.73%, the value is higher than extensive use by summing the pixel value even though it is not significant. The average calculation of wet areas uses a system of about 0.8 seconds or 379 times faster than using millimeter block.